IMPLEMENTASI PROGRAM ANGKUTAN BUS SEKOLAH GRATIS OLEH DINAS PERHUBUNGAN KABUPATEN KAMPAR PROVINSI RIAU TAHUN 2024: TINJAUAN DARI PERSPEKTIF SOSIOLOGI PEMERINTAHAN - Ramzilas Akza; Ishak , (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study was motivated by the high rate of private vehicle use by students without driver’s licenses and the limited availability of public transportation in Kampar Regency, prompting the Kampar Regency Transportation Agency to implement the Free School Bus Program as a form of public service in the transportation sector. This study aims to describe the implementation of the Free School Bus Transportation Program by the Kampar Regency Transportation Agency in Riau Province in 2024 from the perspective of the sociology of governance. The study employs a qualitative descriptive approach with data collection techniques involving interviews and documentation. Informants were selected using purposive sampling, while data analysis was conducted using the Miles and Huberman interactive model. This study utilized William N. Dunn’s policy implementation theory and Max Weber’s theory of social action. The results indicate that the program has not yet been fully optimized. The available fleet capacity is insufficient to meet demand, service coverage is not yet equitable across all sub-districts, and instances of overcrowding continue to occur repeatedly. From the perspective of the sociology of governance through Max Weber’s theory of social action, the implementation of this program indicates that both the local government and the community act rationally; however, government policies have not yet been optimal in changing community habits. This study recommends shifting from a beschikking (decision) to a regeling (regulation), expanding the fleet, extending service routes, and intensifying outreach to all stakeholders. Therefore, it is recommended to make fundamental changes to the policy by shifting from a beschikking to a regeling, expanding the fleet, extending service routes, and enhancing outreach efforts to the public and stakeholders. Keywords: Implementation, School Bus, Department Of Transportation.